2003
DOI: 10.1093/toxsci/kfh017
|View full text |Cite
|
Sign up to set email alerts
|

Serum Hormone Characterization and Exogeneous Hormone Rescue of Bromodichloromethane-Induced Pregnancy Loss in the F344 Rat

Abstract: Previously, we demonstrated that bromodichloromethane (BDCM), a drinking water disinfection by-product, causes pregnancy loss in F344 rats when given on gestational days (GD) 6-10, encompassing the luteinizing hormone (LH)-dependent period of pregnancy (GD 7-10). Pregnancy loss, i.e., full-litter resorption, was associated with reduced serum progesterone levels; however, we were unable to identify an effect on serum LH. Here, we reevaluated serum LH levels using the more sensitive technique, DELFIA(R). We furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…These substances can disrupt the activation of hormone dependent pathways required for male genital development and induce abnormalities of the penis 38. Bielmeier et al 39 40 demonstrated that exposure to bromodichloromethane (BDCM), a species of THM, causes pregnancy loss in rats. This BDCM-induced pregnancy loss was associated with reductions in luteinising hormone and a corresponding decrease in progesterone.…”
Section: Discussionmentioning
confidence: 99%
“…These substances can disrupt the activation of hormone dependent pathways required for male genital development and induce abnormalities of the penis 38. Bielmeier et al 39 40 demonstrated that exposure to bromodichloromethane (BDCM), a species of THM, causes pregnancy loss in rats. This BDCM-induced pregnancy loss was associated with reductions in luteinising hormone and a corresponding decrease in progesterone.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of elimination depends on the amount of fat a person has (World Health Organisation, ) and, as South Asian populations have more fat mass than Europeans (Deurenberg, Deurenberg‐Yap, & Guiricci, ; Stanfield, Wells, Fewtrell, Frost, & Leon, ), the Pakistani‐origin mothers in our sample may have retained DBPs in their bodies for longer, resulting in greater physiological impact. The compounds may impact breast development and lactation (Bielmeier, Best, & Narotsky, ; Rosen‐Carole et al, ) and may transfer from mother to infant (Batterman, Zhang, Wang, & Franzblau, ), potentially altering the taste and acceptability of breastmilk (Office of Environmental Health Hazard Assessment California Environmental Protection Agency, ). Alternatively, rather than being driven by physiological variation, the observed ethnic differences could be explained by social factors not controlled for, for example, diet and stress (Smith et al, ), or even fertility (although further data exploration shows this to be unlikely [results available on request]).…”
Section: Discussionmentioning
confidence: 99%
“…Chloroform (CHCl 3 ), bromoform (CHBr 3 ), bromodichloromethane (CHCl 2 Br), and dibromochloromethane (CHClBr 2 ) are the four compounds belonging to the group of THMs [1][2][3][4]. The presence of THMs in chlorinated drinking water and their lifetime exposure on humans have raised a great concern due to its carcinogenicity and recognition as potential risk to human health [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Several epidemiologic studies have suggested a linkage between THMs exposure and risk of bladder, colon, and rectum cancers [5,13].…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiologic studies have suggested a linkage between THMs exposure and risk of bladder, colon, and rectum cancers [5,13]. Exposure to THMs is also found to be associated with adverse reproductive outcomes [12,13]. The non-cancer effects of THMs are jaundice, *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%